Implementasi Pemanfaatan Media Sosial Dalam Pengembangan Desa Wisata Menari Tambaknegara - Akbar Ilham Adi Pangestu; Faraby Muhammad Zabaril; Diego Agung Laksono; Dea Nur Safitri; Jihan Amalia; Anggun Mely Mustika; Sri Rahayu; Dian Siska Verawati; Joni Prayogi; Najmudin Najmudin (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Activities in this tourist village are a university service program which aims to contribute to developing the tourist village. Apart from that, students can collaborate and interact directly with all parties starting from village officials, Pokdarwis to village communities and utilize existing facilities to apply the knowledge they have acquired. The objects of activity as partners are several parties related to the Tambaknegara Tourism Village, Rawalo District, Banyumas Regency with an activity period of one month. The output of the program implemented includes social media development starting from creating social media accounts, content and promotion of tourist villages. The conclusion from this activity is that the Tambaknegara Tourism Village has tourism potential that can be developed and introduced more widely through the use of information technology, one of which is through social media. The role of various parties still needs to be increased in introducing this tourist village so that more people visit this tourist village.